PEMBERDAYAAN PELAYAN KHUSUS DI GEREJA DALAM UPAYA PENGENDALIAN BUDAYA MAKAN DAN FAKTOR RISIKO SINDROM METABOLIK DI KOTA TOMOHON - Rudolf B. Purba; Fred A. Rumagit; Irza N. Ranti (POLTEKKES KEMENKES MANADO, 2016)
The main risk factors that lead to the occurrence of non-communicable diseases arehypertension, high blood glucose, obesity and abnormal blood fats. The prevalence ofmetabolic syndrome adult population ≥15 years in the province of North Sulawesi of 28%,exceeding the national prevalence rate of 18.8%, the lowest in Bolaang Mongondow16.6% and the highest at 36.2% Tomohon.The research objective is to make religious leaders as promoters of nutrition programmedin delivering nutrition promotion related dietary risk factors which increased the risk ofmetabolic syndrome through education and counseling efforts. Benefits of the research isto increase the level of acceptance, community participation and increasing the role ofreligious leaders in the effort to control the risk factors for metabolic syndrome throughpromotion of nutrition and health implications for disease.This type of research is the study design quasy Experiment Preeksperiment using preand post test one group design. A sample size of 40 people, the sampling technique isbased on systematic random sampling.The conclusion of this study is special maid church can be used as a promoter of nutritionin delivering nutrition promotion related metabolic syndrome risk factor control.